Cellulose nanocrystalline composite material as well as preparation method and application thereof

Through the composite of Hearst fluorescent dye and polyhydroxy compounds with good compatibility with cellulose nanocrystals, the problem of poor compatibility with cellulose nanocrystals and fluorescent dyes is solved, and the fluorescent performance and mechanical properties of composite materials are improved, thus reducing the fluorescence performance and mechanical properties of composite materials. Preparation costs are achieved and responsiveness to acid and alkaline and humidity stimuli are enhanced.

CN119144053APending Publication Date: 2024-12-17SHENZHEN UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411189495.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

There is poor compatibility between cellulose nanocrystals and fluorescent dyes, resulting in poor fluorescence performance and anti-counterfeiting effects of composite materials, and chemical modification increases the preparation cost.

Method used

The composite material is prepared by evaporation-induced self-assembly method to avoid chemistry by chemistry by using Hearst fluorescent dye (Hoechst dye) with cellulose nanocrystals. Modification and organic dispersants for improved compatibility and mechanical properties.

Benefits of technology

The good compatibility between cellulose nanocrystals and fluorescent dyes is achieved, the fluorescence and mechanical properties of the composite material are improved, the preparation cost is reduced, and the response sensitivity to acid, alkali and humidity stimulation is given.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144053A_ABST
    Figure CN119144053A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and provides a cellulose nanocrystalline composite material as well as a preparation method and application thereof. The cellulose nanocrystal composite material provided by the invention comprises cellulose nanocrystals and a fluorescent dye, and the fluorescent dye comprises a Hurst fluorescent dye. According to the present invention, the hydrophilic Hurst fluorescent dye is selected to be compounded with the cellulose nanocrystal, such that the composite material with characteristics of circular polarization fluorescence property, phosphorescence emission property and high fluorescence quantum yield is provided, and the material is environmentally friendly, has small influence on the environment during preparation and use, and has great application potential in the anti-counterfeiting field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of composite materials, and in particular relates to a cellulose nanocrystal composite material and a preparation method and application thereof. Background Art

[0002] Cellulose nanocrystals are a type of nano-scale material extracted from natural fibers (such as cellulose in plants and animals), which has the characteristics of high crystallinity, high purity, high strength, and high elastic modulus. Cellulose nanocrystals have a one-dimensional rod-like structure, with a diameter usually ranging from a few nanometers to tens of nanometers, and a length of hundreds of nanometers or even longer. They also have unique optical properties, and their suspensions can self-assemble to form cholesteric liquid crystal structures, and exhibit circularly polarized light characteristics and structural colors. This structural color is formed by the interference and diffraction of light, and can present bright rainbow colors. This structural color can change under stimulation and has an iridescent effect, so it has broad application prospects in display, anti-counterfeiting, decoration and other fields.

[0003] Although cellulose nanocrystals have unique optical properties, their anti-counterfeiting effect may be relatively simple. In practical applications, they often need to be combined with other anti-counterfeiting technologies to improve the anti-counterfeiting effect. Fluorescent dyes are often used as an ideal anti-counterfeiting material because of their many excellent properties, such as strong fluorescence emission and anti-counterfeiting performance. Cellulose nanocrystals themselves do not have fluorescent properties, but by compounding with fluorescent dyes, they can be given unique fluorescent properties, which can enhance their anti-counterfeiting effect. However, fluorescent dyes used for anti-counterfeiting markings are often hydrophobic, and these dyes have better solubility in organic solvents, while cellulose nanocrystals themselves are hydrophilic and have good dispersibility and stability in water. Therefore, cellulose nanocrystals have poor compatibility with commonly used fluorescent dyes. In order to improve their compatibility with organic fluorescent dyes, they usually need to be chemically modified, and chemical modification will undoubtedly greatly increase the preparation cost of the material. Summary of the invention

[0004] The purpose of the present application is to provide a cellulose nanocrystal composite material and a preparation method and application thereof, aiming to provide a composite material with good compatibility between cellulose nanocrystals and fluorescent dyes.

[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0006] In a first aspect, an embodiment of the present application provides a cellulose nanocrystal composite material, comprising cellulose nanocrystals and a fluorescent dye composited with the cellulose nanocrystals, wherein the fluorescent dye comprises a Hoechst fluorescent dye, and the structural formula of the Hoechst fluorescent dye is shown in Formula I:

[0007]

[0008] Wherein, R is selected from one of hydroxyl, C1~fC6 alkoxy, and N,N-dimethylamino.

[0009] The cellulose nanocrystal composite material provided in the embodiment of the present application is doped with a non-toxic fluorescent dye Hoechst fluorescent dye (Hoechst dye) with good compatibility with cellulose nanocrystals to construct a green and environmentally friendly circularly polarized luminescent material. The composite material has circularly polarized fluorescence properties and phosphorescence emission properties and can be used in the field of anti-counterfeiting.

[0010] In some embodiments, R in Formula I is selected from at least one of hydroxyl, ethoxy, and N,N-dimethylamino. When R is selected from hydroxyl, the Hoechst fluorescent dye is Hoechst fluorescent dye 33258; when R is selected from ethoxy, the Hoechst fluorescent dye is Hoechst fluorescent dye 33342; when R is selected from N,N-dimethylamino, the Hoechst fluorescent dye is Hoechst fluorescent dye 34580. The above three Hoechst fluorescent dyes are more common and widely used in the Hoechst series of dyes.

[0011] In some embodiments, the cellulose nanocrystal composite material further comprises a polyhydroxy compound, wherein the polyhydroxy compound is filled between the cellulose nanocrystals; the polyhydroxy compound comprises at least one of polyethylene glycol, polypropylene glycol, glycerol, glucose, chitosan, fructose, and xylose.

[0012] By introducing the above-mentioned polyhydroxy compounds, the hydrogen bonding effect between the molecules of the composite material is enhanced, the mechanical properties and stability of the composite material are enhanced, and the response sensitivity of the composite material to acid, alkali and humidity is improved.

[0013] In some embodiments, the polyol includes polyethylene glycol, and the number average molecular weight of the polyethylene glycol is 10000 g / mol to 30000 g / mol; and / or, the mass ratio of the cellulose nanocrystal to the polyol is (5 to 15): 1. The polyethylene glycol within the above number average molecular weight range has moderate viscosity and fluidity, which enables it to be more easily mixed with cellulose nanocrystals and fluorescent dyes to form a uniform composite, so that the composite material has better mechanical properties. At the same time, the polyethylene glycol with the above number average molecular weight can protect the fluorescent dye from the influence of the external environment, make the fluorescent dye stably emit light, and improve the fluorescence stability and reliability of the composite material.

[0014] In some embodiments, the mass ratio of the cellulose nanocrystals to the fluorescent dye is (1000-2000): 1. In this way, the composite material can have better fluorescence properties and mechanical properties, and can be more sensitive to external stimuli.

[0015] In a second aspect, the present invention provides a method for preparing a cellulose nanocrystal composite material, comprising the following steps: preparing a cellulose nanocrystal suspension and a fluorescent dye solution respectively; the fluorescent dye in the fluorescent dye solution comprises a Hoechst fluorescent dye, and the structural formula of the Hoechst fluorescent dye is shown in Formula I:

[0016]

[0017] Wherein, R is selected from at least one of hydroxyl, C1-C6 alkoxy, and N,N-dimethylamino; the cellulose nanocrystal suspension is mixed with the fluorescent dye solution and then evaporated to induce self-assembly to obtain the cellulose nanocrystal composite material.

[0018] Since the Hoechst dye with good compatibility with cellulose nanocrystals is selected in the embodiment of the present application, there is no need to chemically modify the cellulose nanocrystals or add an organic dispersant, so the fluorescent dye and the cellulose nanocrystals can be evenly compounded, thereby greatly reducing the preparation cost.

[0019] In some embodiments, a polyhydroxy compound is added during the mixing of the cellulose nanocrystal suspension and the fluorescent dye solution, and the polyhydroxy compound includes at least one of polyethylene glycol, glycerol, glucose, chitosan, fructose, and xylose. The addition of the polyhydroxy compound makes the hydrogen bonding effect more significant, helps to form a stable self-assembly structure, and gives the composite material better fluorescence properties.

[0020] In some embodiments, in the cellulose nanocrystal suspension, the mass fraction of cellulose nanocrystals is 2% to 5%; and / or, the pH value of the cellulose nanocrystal suspension is 2 to 4; and / or, in the fluorescent dye solution, the mass concentration of the fluorescent dye is 0.5 mg / mL to 3 mg / mL; and / or, the mass ratio of the cellulose nanocrystal suspension to the fluorescent dye solution is (400 to 600):1. The mass ratio of the above-mentioned cellulose nanocrystal suspension to the fluorescent dye solution can enable the fluorescent dye molecules to be evenly dispersed in the cellulose nanocrystal suspension, which helps to maintain the orderliness of the self-assembled structure of the cellulose nanocrystals, while promoting the combination and self-assembly between the components. By optimizing the above-mentioned preparation conditions, the structure and properties of the composite material can be regulated, which helps to evenly distribute and efficiently load the Hoechst dye in the cellulose nanocrystal network, thereby further improving the fluorescence quantum yield.

[0021] In some embodiments, the preparation step of the cellulose nanocrystal suspension includes: mixing a cellulose-containing biomass substrate with a sulfuric acid solution, and then reacting for 1h to 2h at a temperature of 40°C to 50°C and a stirring speed of 400rpm / min to 600rpm / min; wherein the concentration of the sulfuric acid solution is 62wt% to 64wt%, and the mass volume ratio of the cellulose-containing biomass substrate to the sulfuric acid solution is 1g: (5 to 15)mL. The conditions of acid hydrolysis have an important influence on the size distribution, morphology and surface chemical properties of cellulose nanocrystals. By adopting the above preparation scheme, cellulose nanocrystals with concentrated size distribution and rod-shaped morphology can be hydrolyzed to obtain, which is conducive to the formation of a more regularly and closely arranged self-assembled structure.

[0022] In a third aspect, embodiments of the present application provide an application of a cellulose nanocrystal composite material as described in the first aspect and / or a cellulose nanocrystal composite material prepared by the preparation method of the cellulose nanocrystal composite material as described in the second aspect in anti-counterfeiting materials, sensors, and detectors. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 It is a fluorescence photograph and a polarizing microscope photograph of the cellulose nanocrystal composite material provided in Example 1 of the present application after TEA / HCl steam treatment; wherein TEA refers to triethylamine, representing alkaline stimulation; HCl refers to hydrochloric acid, representing acid stimulation;

[0025] Figure 2 is the fluorescence spectrum of the cellulose nanocrystal composite material provided in Example 1 of the present application before and after heating and drying; wherein Hoechst33258@CNC refers to a composite material of cellulose nanocrystals and Hoechst33258;

[0026] Figure 3 is the fluorescence spectrum of the cellulose nanocrystal composite material provided in Examples 1, 2, and 3 of the present application after stimulation by TEA / HCl vapor;

[0027] Figure 4 is a reversible cycle diagram of the cellulose nanocrystal composite material provided in Example 1 of the present application after TEA / HCl vapor stimulation;

[0028] Figure 5It is the fluorescence spectrum of the cellulose nanocrystal composite material after TEA / HCl vapor stimulation and the anti-counterfeiting identification diagram of the reversible cycle design provided in Examples 1, 3 and 4 of the present application. DETAILED DESCRIPTION

[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0030] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0031] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0032] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0033] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0034] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0035] Composite materials of cellulose nanocrystals and fluorescent dyes have unique optical properties and fluorescent characteristics, and have certain application potential in the field of anti-counterfeiting. However, due to their nanoscale size, cellulose nanocrystals have extremely high polarity and surface energy, which makes their interaction with fluorescent dyes complicated and difficult. Fluorescent dyes usually have specific chemical structures and functional groups, and the polarity of fluorescent dyes may vary due to their chemical structure. When the surface properties and polarity of fluorescent dyes differ greatly from those of cellulose nanocrystals, the compatibility between the two will deteriorate, and poor compatibility will affect the fluorescent properties of the composite material.

[0036] Based on this, the embodiment of the present application provides a cellulose nanocrystal composite material, including cellulose nanocrystals and a fluorescent dye composited with the cellulose nanocrystals; the fluorescent dye includes a Hoechst fluorescent dye, and the structural formula of the Hoechst fluorescent dye is shown in Formula I:

[0037]

[0038] Wherein, R is selected from one of hydroxyl, C1-C6 alkoxy, and N,N-dimethylamino.

[0039] The term "C1-C6 alkoxy" refers to a group formed by connecting an alkyl group containing 1 to 6 carbon atoms to an oxygen atom. For example, C1-C6 alkoxy includes, but is not limited to, methoxy, ethoxy, 1-propoxy, 2-propoxy, 1-butoxy, 1-pentoxy, 1-hexoxy, and the like.

[0040] Hoechst fluorescent dyes belong to the benzimidazole class of compounds and are a class of hydrophilic fluorescent dyes. Their molecules contain a variety of hydrophilic groups, such as amino and hydroxyl groups. These hydrophilic groups are also polar groups and are easy to form hydrogen bonds with other polar molecules, so Hoechst dyes also have a certain polarity. The surface of cellulose nanocrystals is also rich in hydroxyl groups, which not only provide them with strong polarity and hydrophilicity, but also provide abundant reaction sites for complexing with other compounds. Since both Hoechst dyes and cellulose nanocrystals are hydrophilic, they have good compatibility and a certain affinity, which is conducive to interaction between the two. For example, Hoechst dyes can combine with the hydroxyl groups on the surface of cellulose nanocrystals through intermolecular forces such as hydrogen bonds and van der Waals forces to form a stable composite structure.

[0041] Hoechst dye is a blue fluorescent dye that can emit strong blue fluorescence under ultraviolet light excitation. This fluorescent property makes it have unique marking and identification functions in anti-counterfeiting applications. After the Hoechst dye is combined with cellulose nanocrystals, the composite material will emit unique blue fluorescence under ultraviolet light, thereby achieving anti-counterfeiting function. Moreover, due to the good compatibility of the two components of the composite material, the chiral photonic crystal structure of cellulose nanocrystals can enhance the fluorescence signal of the Hoechst dye, so that the fluorescence signal is amplified in the cellulose nanocrystals, thereby improving the sensitivity and accuracy of anti-counterfeiting fluorescence detection.

[0042] The embodiment of the present application selects a hydrophilic Hoechst dye and a cellulose nanocrystal to form a composite material having circularly polarized fluorescence properties and phosphorescent emission properties, and a high fluorescence quantum yield. The composite material responds to both acid-base stimulation and humidity stimulation. Both the Hoechst dye and the cellulose nanocrystal are environmentally friendly and have little impact on the environment during preparation and use, and has great application potential in the field of anti-counterfeiting.

[0043] In some embodiments, R in Formula I is selected from at least one of hydroxyl, ethoxy, and N,N-dimethylamino. When R is selected from hydroxyl, the Hoechst fluorescent dye is Hoechst fluorescent dye 33258; when R is selected from ethoxy, the Hoechst fluorescent dye is Hoechst fluorescent dye 33342; when R is selected from N,N-dimethylamino, the Hoechst fluorescent dye is Hoechst fluorescent dye 34580. The above three Hoechst fluorescent dyes are more common and widely used in the Hoechst series of dyes. They have similar chemical structural basis, can be excited by ultraviolet light of about 350nm, and emit blue or blue-indigo fluorescence near 461nm, and have similar fluorescence properties. Among them, the structural formula of Hoechst fluorescent dye 33258 is shown in Formula II:

[0044]

[0045] The structural formula of Hoechst fluorescent dye 33342 is shown in Formula III:

[0046]

[0047] The structural formula of Hoechst fluorescent dye 34580 is shown in Formula IV:

[0048]

[0049] In some embodiments, the cellulose nanocrystal composite material further includes a polyhydroxy compound, and the polyhydroxy compound is filled between the cellulose nanocrystals; the polyhydroxy compound includes at least one of polyethylene glycol, polypropylene glycol, glycerol, glucose, chitosan, fructose, and xylose.

[0050] By introducing the above-mentioned polyhydroxy compounds, the intermolecular hydrogen bonding of the composite material can be further enhanced. The hydroxyl groups between the components can be tightly bound by intermolecular interactions such as hydrogen bonds to form a more stable composite structure. This composite structure not only enhances the mechanical properties and stability of the composite material, but also promotes the sensitivity of the optical properties to external stimuli. This is because hydrogen bonding is an intermolecular or intramolecular interaction force, which is dynamic and reversible. Under the action of external stimuli (such as acid, alkali, humidity, etc.), hydrogen bonds can be broken and re-formed, and this process is reversible. The breaking and re-formation of hydrogen bonds will lead to changes in the conformation of fluorescent molecules, thereby affecting the shape and position of their fluorescence emission spectrum. The change in hydrogen bonding will also affect the energy transfer path and efficiency between fluorescent molecules, resulting in changes in the color of fluorescent emission. Changes in hydrogen bonding will also change the helical structure of cellulose nanocrystals. This helical structure can selectively reflect light of different wavelengths and produce structural colors. The change in pitch will directly lead to changes in the reflected wavelength, thereby presenting different colors. Therefore, by further introducing polyhydroxy compounds, while enhancing the hydrogen bonding effect, the sensitivity of the response to acid, alkali and humidity is also improved. These hydrogen bonds can change under external stimuli, thus affecting the efficiency of fluorescence energy transfer, achieving reversible changes in fluorescence emission color and cyclic quenching of phosphorescence emission in response to acid-base and humidity stimuli. This property of stimuli-responsiveness to acid-base and humidity can be used in fields such as anti-counterfeiting and humidity and pH sensors.

[0051] In some optional embodiments, the polyol is selected from polyethylene glycol and / or glucose. Polyethylene glycol and glucose have excellent physicochemical properties, biocompatibility and functional diversity. Selecting these two compound components to be introduced into the cellulose nanocrystalline composite material can further enhance the flexibility of the material, enhance the processability of the composite material, reduce the cost of the composite material, etc.

[0052] In some embodiments, the number average molecular weight of polyethylene glycol is 10000 g / mol to 30000 g / mol. As an example, the number average molecular weight of polyethylene glycol can be 10000 g / mol, 15000 g / mol, 20000 g / mol, 25000 g / mol, 30000 g / mol and other typical but non-limiting values. Polyethylene glycol with the above number average molecular weight has a higher molecular weight and higher viscosity, which can enhance the interaction between the components of the composite material, so that the components can be closely combined to form a stable structure, which not only improves the stability of the fluorescent dye in the composite material, but also makes the fluorescent signal more uniform and lasting.

[0053] In some embodiments, the mass ratio of cellulose nanocrystals to polyols is (5-15):1. As an example, the mass ratio of the two can be typical but non-limiting values ​​such as 5:1, 7:1, 9:1, 11:1, 13:1, 15:1, etc. As the content of polyols increases, the flexibility of the composite material will also increase. Polyols can improve the dispersibility and compatibility of the components of the composite material, thereby enhancing the flexibility of the composite material. However, when the content of polyols is too high, the interaction between the components will be weakened, resulting in a decrease in tensile strength. Moreover, the introduction of polyols will also affect the optical properties of the composite material. Controlling the mass ratio of the two within the above range can make the mechanical properties, optical properties, and responsiveness to external stimuli of the composite material better.

[0054] In some embodiments, the mass ratio of cellulose nanocrystals to fluorescent dyes is (1000-2000):1. As an example, the mass ratio of the two can be typical but non-limiting values ​​such as 1000:1, 1200:1, 1400:1, 1600:1, 1800:1, 2000:1. The addition of fluorescent dyes can give the composite material fluorescent properties. As the amount of fluorescent dye added increases, the fluorescence intensity of the composite material will increase, but if the concentration of the fluorescent dye is too high, the fluorescent properties will also decrease, and the internal defects of the composite material may also increase, thereby reducing its mechanical properties. The above-mentioned mass ratio of cellulose nanocrystals to fluorescent dyes can make the composite material have better fluorescent properties and mechanical properties.

[0055] In a second aspect, the present invention provides a method for preparing a cellulose nanocrystal composite material, comprising the following steps: preparing a cellulose nanocrystal suspension and a fluorescent dye solution, respectively, wherein the fluorescent dye in the fluorescent dye solution comprises a Hoechst fluorescent dye, and the structural formula of the Hoechst fluorescent dye is shown in Formula I:

[0056]

[0057] Wherein, R is selected from at least one of hydroxyl, C1-C6 alkoxy, and N,N-dimethylamino; the cellulose nanocrystal suspension is mixed with the fluorescent dye solution and then evaporated to induce self-assembly to obtain a cellulose nanocrystal composite material.

[0058] In order to improve the compatibility and binding force between cellulose nanocrystals and fluorescent dyes, the preparation of the composite material of cellulose nanocrystals and fluorescent dyes may involve complex chemical treatment or physical mixing steps, which increases the complexity and cost of the preparation process. Since the Hoechst dye with good compatibility with cellulose nanocrystals is selected in the embodiment of the present application, the preparation process is simple, there is no need to chemically modify the cellulose nanocrystals, and there is no need to add an organic dispersant to the system, thereby greatly reducing the preparation cost.

[0059] In some embodiments, the evaporation-induced self-assembly process is to place a mixed solution of the cellulose nanocrystal suspension and the fluorescent dye solution in a polystyrene plastic culture dish after stirring for 4 to 8 hours, and evaporate for 4 to 8 days under natural windless conditions to form a film.

[0060] In some embodiments, a polyhydroxy compound is added during the mixing of the cellulose nanocrystal suspension and the fluorescent dye solution, wherein the polyhydroxy compound includes at least one of polyethylene glycol, glycerol, glucose, chitosan, fructose, and xylose, so as to obtain a composite material with enhanced hydrogen bonds.

[0061] In some embodiments, the mass ratio of the cellulose nanocrystal suspension to the polyol is 1000:(1-10). As an example, the mass ratio of the two can be 1000:1, 1000:2, 1000:4, 1000:6, 1000:8, 1000:10 and other typical but non-limiting values. When the mass ratio of the two is controlled within the above range, the hydrogen bond enhancement effect is more significant, which helps to form a stable self-assembled structure.

[0062] In some embodiments, the evaporation-induced self-assembly process is to first mix the cellulose nanocrystal suspension with the fluorescent dye solution, then add the polyhydroxy compound, stir for 4 to 8 hours, and then place it in a polystyrene plastic culture dish, and evaporate for 4 to 8 days under natural windless conditions to form a film. In this way, the photon array of the cellulose nanocrystals is not affected, and the polyhydroxy compound added later has the effect of strengthening the hydrogen bonds, thereby achieving a regular and tight arrangement of the self-assembled structure.

[0063] In some embodiments, the cellulose nanocrystal suspension is a mixed solution of cellulose nanocrystals and water. Since the surface of cellulose nanocrystals is rich in hydroxyl groups, the hydroxyl groups easily form hydrogen bonds with water molecules or other polar molecules. This characteristic enables cellulose nanocrystals to form a relatively stable dispersion system in polar solvents such as water.

[0064] In some embodiments, in the cellulose nanocrystal suspension, the mass fraction of cellulose nanocrystals is 2% to 5%. As an example, the mass fraction can be typical but non-limiting values ​​such as 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc. The mass fraction represents the concentration of the suspension. As the concentration increases, the collision frequency between nanocrystals and with other components increases, which can accelerate the self-assembly process. However, too high a concentration will cause the nanocrystals to begin to aggregate in the suspension to form a more complex structure, which is not conducive to the formation of an ordered structure. Therefore, by controlling the mass fraction within the above range, a more compact and ordered chiral array phase structure can be formed.

[0065] In some embodiments, the pH value of the cellulose nanocrystal suspension is 2 to 4. The pH value of the cellulose nanocrystal suspension affects the stability of the nanocrystals in the medium. Under different pH conditions, the charge state of the nanocrystal surface will change, thereby affecting its dispersibility and stability in water. The charged state of the nanocrystals is adjusted by adjusting the pH value, thereby controlling the repulsive force between the nanocrystal molecules, improving the regular and tight arrangement of the nanocrystals, and helping to improve the fluorescence stability of the composite material. In addition, the regular and tight self-assembled structure can make the material have stronger fluorescence emission or absorption ability at a specific wavelength, thereby improving the recognition and anti-counterfeiting effect of the fluorescent anti-counterfeiting material.

[0066] In some embodiments, the fluorescent dye solution is an aqueous solution of the fluorescent dye, and the mass concentration of the fluorescent dye in the fluorescent dye solution is 0.5 mg / mL to 3 mg / mL. The concentration of the fluorescent dye solution can affect the stability of the self-assembled structure. If the concentration is too high, it may cause the interaction between the fluorescent dye molecules to be too strong, thereby destroying the stability of the self-assembled structure. If the concentration is too low, a relatively loose or open self-assembled structure may be formed. Controlling the concentration of the fluorescent dye solution within the above range can form a more stable self-assembled structure with better fluorescence performance.

[0067] In some embodiments, the mass ratio of the cellulose nanocrystal suspension to the fluorescent dye solution is (400-600):1. As an example, the mass ratio of the two can be typical but non-limiting values ​​such as 400:1, 450:1, 500:1, 550:1, 600:1. If the proportion of the fluorescent dye solution is too high, a large number of fluorescent dye molecules may occupy the space between the cellulose nanocrystals, interfere with the normal arrangement of the nanocrystals, and cause the order of the self-assembled structure to decrease. If the proportion of the fluorescent dye solution is too low, it may affect the fluorescent properties of the composite material. Controlling the mass ratio of the two within the above range can make the fluorescent dye molecules evenly dispersed in the network of cellulose nanocrystals, which helps to improve the order of the self-assembled structure of the material.

[0068] During the preparation process, the above preparation conditions are optimized, and the interaction of the above preparation conditions jointly determines the structure and properties of the composite material. The combination of these conditions helps to achieve uniform distribution and efficient loading of Hoechst dye between cellulose nanocrystals, thereby improving the fluorescence quantum yield.

[0069] By adjusting the above preparation conditions, the forbidden band reflection wavelength of cellulose nanocrystals can be regulated. When cellulose nanocrystals are combined with Hoechst dyes, the forbidden band reflection wavelength of cellulose nanocrystals can be adjusted to match or approach the fluorescence emission wavelength of Hoechst dyes, thereby achieving precise regulation of optical properties. When the fluorescence emission wavelength of Hoechst dyes has a high matching degree with the reflection wavelength position of cellulose nanocrystals, spectral overlap can be achieved to the maximum extent, which is conducive to the photons emitted by the fluorescent dye being used by cellulose nanocrystals and improving energy conversion efficiency. At the same time, high wavelength matching can make more photons be reflected or scattered, thereby enhancing the optical properties of the composite material, improving the brightness of the composite material, and enhancing the visual effect.

[0070] In some embodiments, the step of preparing a cellulose nanocrystal suspension comprises: mixing a cellulose-containing biomass substrate with a sulfuric acid solution and performing a hydrolysis reaction to obtain. Specifically, a cellulose-containing biomass substrate with a mass volume ratio of 1g: (5-15) mL is mixed with a sulfuric acid solution. The cellulose-containing biomass substrate can be listed as absorbent cotton, corn stalks, wheat stalks, wood, etc. The concentration of the sulfuric acid solution is 62wt% to 64wt%, heated at 40°C to 50°C, and reacted for 1 to 2 hours under mechanical stirring at 400rpm / min to 600rpm / min. After the reaction is completed, the solution is poured into water to quench the reaction, and then allowed to stand and precipitate. Then take the lower layer of suspension, centrifuge it at a speed of 8000rpm / min to 12000rpm / min for 3 to 4 times, collect the upper turbid liquid, dialyze it in a dialysis bag until the pH is stable, and then concentrate the dialysate to a concentration of 2% to 5% under heating and stirring conditions at 30°C to 40°C. Then you can also filter it with a 0.2μm to 0.3μm water filter membrane and store it for later use.

[0071] In the third aspect, the embodiments of the present application provide an application of the above-mentioned cellulose nanocrystal composite material in anti-counterfeiting materials, sensors, and detectors. The cellulose nanocrystal composite material emits blue fluorescence under ultraviolet (UV) irradiation. When the composite material meets water, the fluorescence color shifts to blue, and returns to the original color after evaporation; when the composite material meets acid, the fluorescence color shifts to green, and returns to the original color after neutralization; when the composite material meets alkali, the fluorescence color shifts to blue, and returns to the original color after neutralization.

[0072] The following describes the invention in conjunction with specific embodiments.

[0073] Example 1

[0074] This embodiment provides a cellulose nanocrystal composite material, including cellulose nanocrystals and Hoechst fluorescent dye 33258, wherein the mass ratio of the cellulose nanocrystals to the Hoechst fluorescent dye 33258 is 1500:1.

[0075] The preparation method of the above-mentioned cellulose nanocrystal composite material comprises the following steps:

[0076] (1) Take 15g of absorbent cotton pulp, cut it into pieces and put it into a wall-breaking machine, add ultrapure water to fully break it, and then dry it in a 50℃ oven for two days to remove moisture; after drying, the cotton balls are further broken and crushed and transferred to a 250mL round-bottom flask, 150mL of 64wt% sulfuric acid solution is added thereto, placed in a 45℃ water bath for heating, and reacted for 1.5h under mechanical stirring at 500rpm / min. After the reaction is completed, the solution is poured into 10 times the amount of ultrapure water to quench the reaction, and allowed to stand for one day. Then take the lower layer of suspension, centrifuge it at a speed of 10000rpm / min for 3-4 times with a high-speed centrifuge, collect the upper layer of turbid liquid, and dialyze it in an 8000kDa dialysis bag until the pH is stable. Finally, the dialysate was transferred to a beaker, concentrated under heating and stirring conditions at 35°C, filtered with a water filter syringe filter with a pore size of 0.22 μm and stored in a refrigerator for later use. The pH value of the cellulose nanocrystal suspension was 3, and the mass fraction of the cellulose nanocrystals was 3%.

[0077] (2) 4 mL of the above cellulose nanocrystal suspension was added with 80 μL of a 1 mg / mL aqueous solution of Hoechst fluorescent dye 33258 under stirring, and the mixture was transferred to a 35 mm polystyrene plastic culture dish after stirring for 6 h. The mixture was evaporated for 6 days under natural windless conditions to form a film, thereby obtaining a cellulose nanocrystal composite material.

[0078] Example 2

[0079] The difference between Example 2 and Example 1 is that the cellulose nanocrystal composite material includes cellulose nanocrystals and Hoechst fluorescent dye 33342, and the mass ratio of cellulose nanocrystals to Hoechst fluorescent dye 33342 is 1500:1.

[0080] The difference between its preparation method and Example 1 is: 4 mL of cellulose nanocrystal suspension is taken, 80 μL of a 1 mg / mL Hoechst fluorescent dye 33342 fluorescent dye aqueous solution is added thereto under stirring, and after stirring for 6 hours, the mixture is transferred to a 35 mm polystyrene plastic culture dish and evaporated for 6 days under natural windless conditions to form a film, thereby obtaining a cellulose nanocrystal composite material.

[0081] Example 3

[0082] The difference between Example 3 and Example 1 is that the cellulose nanocrystal composite material comprises cellulose nanocrystals and Hoechst fluorescent dye 34580, and the mass ratio of cellulose nanocrystals to Hoechst fluorescent dye 34580 is 1500:1.

[0083] The difference between its preparation method and Example 1 is that: 4 mL of cellulose nanocrystal suspension is taken, 80 μL of a 1 mg / mL Hoechst fluorescent dye 34580 fluorescent dye aqueous solution is added thereto under stirring, and after stirring for 6 hours, the mixture is transferred to a 35 mm polystyrene plastic culture dish and evaporated for 6 days under natural windless conditions to form a film, thereby obtaining a cellulose nanocrystal composite material.

[0084] Example 4

[0085] The difference between Example 4 and Example 1 is that the cellulose nanocrystal composite material includes cellulose nanocrystals, Hoechst fluorescent dye 33258 and glucose, and the mass ratio of cellulose nanocrystals to Hoechst fluorescent dye 33258 is 1500:1; the mass ratio of cellulose nanocrystals to glucose is 9:1.

[0086] The difference between its preparation method and Example 1 is that: 4 mL of the above-mentioned cellulose nanocrystal suspension is taken, 80 μL of a 1 mg / mL Hoechst fluorescent dye 33258 fluorescent dye aqueous solution is added thereto under stirring, and then 0.013 g of glucose is added. After mixing and stirring for 6 hours, the mixture is transferred to a 35 mm polystyrene plastic culture dish and evaporated for 6 days under natural windless conditions to form a film, thereby obtaining a cellulose nanocrystal composite material.

[0087] Example 5

[0088] The difference between Example 5 and Example 4 is that its cellulose nanocrystal composite material includes cellulose nanocrystals, Hoechst fluorescent dye 33258 and polyethylene glycol (number average molecular weight is 20000 g / mol), the mass ratio of cellulose nanocrystals to Hoechst fluorescent dye 33258 is 1500:1; the mass ratio of cellulose nanocrystals to polyethylene glycol is 9:1.

[0089] The difference between its preparation method and Example 1 is that: 4 mL of the above-mentioned cellulose nanocrystal suspension is taken, 80 μL of a 1 mg / mL Hoechst fluorescent dye 33258 fluorescent dye aqueous solution is added thereto under stirring, and then 0.013 g of polyethylene glycol 20000 is added. After mixing and stirring for 6 hours, the mixture is transferred to a 35 mm polystyrene plastic culture dish and evaporated for 6 days under natural windless conditions to form a film to obtain a cellulose nanocrystal composite material.

[0090] Example 6

[0091] The difference between Example 6 and Example 5 is that the cellulose nanocrystal composite material includes cellulose nanocrystals, Hoechst fluorescent dye 33258 and polyethylene glycol (number average molecular weight is 20000 g / mol), the mass ratio of cellulose nanocrystals to Hoechst fluorescent dye 33258 is 1000:1; the mass ratio of cellulose nanocrystals to polyethylene glycol is 5:1.

[0092] The difference between its preparation method and Example 1 is that: 2.67 mL of the above-mentioned cellulose nanocrystal suspension is taken, 80 μL of a 1 mg / mL Hoechst fluorescent dye 33258 fluorescent dye aqueous solution is added thereto under stirring, and then 0.016 g of polyethylene glycol 20000 is added. After mixing and stirring for 6 hours, the mixture is transferred to a 35 mm polystyrene plastic culture dish and evaporated for 6 days under natural windless conditions to form a film to obtain a cellulose nanocrystal composite material.

[0093] Example 7

[0094] The difference between Example 7 and Example 5 is that its cellulose nanocrystal composite material includes cellulose nanocrystals, Hoechst fluorescent dye 33258 and polyethylene glycol (number average molecular weight is 20000 g / mol), the mass ratio of cellulose nanocrystals to Hoechst fluorescent dye 33258 is 2000:1; the mass ratio of cellulose nanocrystals to polyethylene glycol is 15:1.

[0095] The difference between its preparation method and Example 1 is that: 5.33 mL of the above-mentioned cellulose nanocrystal suspension is taken, 80 μL of a 1 mg / mL Hoechst fluorescent dye 33258 fluorescent dye aqueous solution is added thereto under stirring, and then 0.035 g of polyethylene glycol 20000 is added. After mixing and stirring for 6 hours, the mixture is transferred to a 35 mm polystyrene plastic culture dish and evaporated for 6 days under natural windless conditions to form a film to obtain a cellulose nanocrystal composite material.

[0096] Comparative Example 1

[0097] This comparative example provides a cellulose nanocrystal film, and its preparation method is different from that of Example 1 in that: 4 mL of cellulose nanocrystal suspension is taken, stirred for 6 hours, and then transferred to a 35 mm polystyrene plastic culture dish, and evaporated for 6 days under natural windless conditions to form a film, thereby obtaining the cellulose nanocrystal film.

[0098] Performance Testing

[0099] The materials prepared in Examples 1 to 7 and Comparative Example 1 were tested using the following characterization methods:

[0100] (1) Fluorescence images were taken using a fluorescence microscope, and polarizing microscopy images were taken using a polarizing microscope.

[0101] (2) Fluorescence (PL) spectroscopy: The fluorescence spectrometer was used for detection, with excitation wavelengths of 320 nm and 360 nm, respectively, and a scanning speed of 4 nm / s.

[0102] Depend on Figure 1 to Figure 5It can be seen that the composite materials of Examples 1 to 5 have multiple stimulus responsiveness to acid, alkali and humidity. And the stimulus response is reversible multiple times. Among them, Figure 1 (a) is a polarizing microscope image of the cellulose nanocrystal composite material (film) of Example 1 after being treated with hydrochloric acid (HCl) vapor. Figure 1 (b) is a polarizing microscope image of the cellulose nanocrystal composite material (film) of Example 1 after being treated with triethylamine (TEA) vapor. Figure 1 (c) is a fluorescence microscopy image of the cellulose nanocrystal composite material (film) of Example 1 after being treated with hydrochloric acid (HCl) vapor. Figure 1 (d) is a fluorescence microscope image of the cellulose nanocrystal composite material (film) of Example 1 after being treated with triethylamine (TEA) vapor. As can be seen from the figure, the cellulose nanocrystal composite material (film) of Example 1 emits green fluorescence after acid (HCl) stimulation (fumigation with saturated hydrochloric acid vapor for 0.5 h), and emits blue fluorescence after alkali (TEA) stimulation (fumigation with saturated triethylamine vapor for 0.5 h), and can respond to acid and alkali stimulation.

[0103] Figure 2 The fluorescence spectra of the cellulose nanocrystal composite material (film) of Example 1 under dry and hygroscopic conditions. In the dry state, the peak of the fluorescence emission spectrum of the composite film is near 410nm, and the corresponding fluorescence microscope photo of the composite film shows blue; under hygroscopic conditions, the peak of the fluorescence emission spectrum of the composite film is near 510nm, and the corresponding fluorescence microscope photo of the composite film shows green. It can be seen from the figure that the cellulose nanocrystal composite material (film) of Example 1 can emit blue fluorescence under dry conditions (placed in an environment with a humidity of less than 40% RH for 0.5h), and can emit green fluorescence under hygroscopic conditions (placed in an environment with a humidity of more than 80% RH for 0.5h), and can respond to humidity.

[0104] Figure 3 The fluorescence spectra of the composite membranes of Example 1 (Hoechst33258@CNC), Example 2 (Hoechst33342@CNC), and Example 3 (Hoechst34580@CNC) after hydrochloric acid (HCl) / triethylamine (TEA) vapor treatment are shown in the figure. As can be seen from the figure, the peak values ​​of the fluorescence emission spectra of the three cellulose nanocrystal composite materials (membranes) after acid (HCl) stimulation are all located at about 500nm-540nm, and the peak values ​​of the fluorescence emission spectra after alkali (TEA) stimulation are all located at about 420nm-460nm, indicating that the three composite membranes can respond to acid-base stimulation.

[0105] Figure 4This is a reversible cycle diagram of the fluorescence spectrum of the cellulose nanocrystal composite film (Hoechst33258@CNC) of Example 1 after hydrochloric acid (HCl) / triethylamine (TEA) vapor cycle stimulation, indicating that the composite film has multiple reversibility in response to stimulation.

[0106] Figure 5 The anti-counterfeiting label printed with "Shenzhen University" prepared by using the cellulose nanocrystal composite material (Hoechst33258@CNC) of Example 1 can be prepared by: pouring the cellulose nanocrystal composite material into a template printed with the font "Shenzhen University", and then forming the anti-counterfeiting label by evaporation self-assembly. After the anti-counterfeiting label is dried, it emits blue fluorescence under UV light, and after stopping UV irradiation, green phosphorescence will remain. In the figure, A, B, C, and D represent the materials of Example 1, Example 3, Example 4, and Comparative Example 1, respectively. Among them, under UV light irradiation, due to the high humidity in Shenzhen, the initial state of the composite film corresponding to A, B, and C all emits green fluorescence, and D does not emit fluorescence because it does not have a composite Hoechst fluorescent dye. When the composite film corresponding to A and B is stimulated by triethylamine (TEA) vapor, the fluorescence emitted changes from green to blue, and after drying, it still emits blue fluorescence, and then after moisture absorption, the fluorescence color of A, B, and C changes from blue to blue-green, and after being stimulated by hydrochloric acid (HCl) vapor, the fluorescence color of A, B, and C changes from blue-green to green. These all show that the composite film of the embodiment of the present application has acid-base and humidity multiple stimulus responsiveness, and the stimulus response is reversible.

[0107] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A cellulose nanocrystal composite material, characterized in that: It includes cellulose nanocrystals and a fluorescent dye compounded with the cellulose nanocrystals; the fluorescent dye includes a Hoechst fluorescent dye, and the structural formula of the Hoechst fluorescent dye is shown in Formula I: Wherein, R is selected from at least one of hydroxyl, C1-C6 alkoxy, and N,N-dimethylamino.

2. The cellulose nanocrystal composite material according to claim 1, characterized in that In formula I, R is selected from at least one of hydroxyl, ethoxy and N,N-dimethylamino.

3. The cellulose nanocrystal composite material according to claim 1, characterized in that The cellulose nanocrystal composite material further comprises a polyhydroxy compound, and the polyhydroxy compound is filled between the cellulose nanocrystals; the polyhydroxy compound comprises at least one of polyethylene glycol, glycerol, glucose, chitosan, fructose and xylose.

4. The cellulose nanocrystal composite material according to claim 3, characterized in that The polyhydroxy compound includes polyethylene glycol, and the number average molecular weight of the polyethylene glycol is 10000 g / mol to 30000 g / mol; And / or, the mass ratio of the cellulose nanocrystals to the polyhydroxy compound is (5-15):

1.

5. The cellulose nanocrystal composite material according to any one of claims 1 to 4, characterized in that The mass ratio of the cellulose nanocrystals to the fluorescent dye is (1000-2000):

1.

6. A method for preparing a cellulose nanocrystal composite material, characterized in that: The following steps are involved: A cellulose nanocrystal suspension and a fluorescent dye solution are prepared respectively. The fluorescent dye in the fluorescent dye solution includes a Hoechst fluorescent dye. The structural formula of the Hoechst fluorescent dye is shown in Formula I: Wherein, R is selected from at least one of hydroxyl, C1-fC6 alkoxy, and N,N-dimethylamino; The cellulose nanocrystal suspension is mixed with the fluorescent dye solution and then evaporated to induce self-assembly to obtain the cellulose nanocrystal composite material.

7. The method for preparing the cellulose nanocrystal composite material according to claim 6, characterized in that: In the process of mixing the cellulose nanocrystal suspension with the fluorescent dye solution, a polyhydroxy compound is also added, and the polyhydroxy compound includes at least one of polyethylene glycol, glycerol, glucose, chitosan, fructose, and xylose.

8. The method for preparing a cellulose nanocrystal composite material according to any one of claims 6 to 7, characterized in that: In the cellulose nanocrystal suspension, the mass fraction of cellulose nanocrystals is 2% to 5%; and / or, the pH value of the cellulose nanocrystal suspension is 2 to 4; And / or, in the fluorescent dye solution, the mass concentration of the fluorescent dye is 0.5 mg / mL to 3 mg / mL; And / or, the mass ratio of the cellulose nanocrystal suspension to the fluorescent dye solution is (400-600):

1.

9. The method for preparing a cellulose nanocrystal composite material according to any one of claims 6 to 7, characterized in that: The preparation steps of the cellulose nanocrystal suspension include: mixing a cellulose-containing biomass substrate with a sulfuric acid solution, and then reacting for 1h to 2h at a temperature of 40°C to 50°C and a stirring speed of 400rpm / min to 600rpm / min; wherein the concentration of the sulfuric acid solution is 62wt% to 64wt%, and the mass volume ratio of the cellulose-containing biomass substrate to the sulfuric acid solution is 1g:(5-15)mL.

10. Use of the cellulose nanocrystal composite material according to any one of claims 1 to 5 and / or the cellulose nanocrystal composite material prepared by the preparation method of the cellulose nanocrystal composite material according to any one of claims 6 to 9 in anti-counterfeiting materials, sensors or detectors.

Citation Information

Cited By

  • Circularly polarized luminescent material and preparation method and application thereof

    CN119931633A

  • Circularly polarized luminescent material, preparation method and application thereof

    CN119931633B

  • A dynamically regulated circularly polarized luminescent cellulose ionic liquid gel with structural color and a preparation method and application thereof

    CN122973658A